Letter
012a-0135-001 Prime Minister 10, Downing Street Whitehall, 1st February, 1938. Dear Sir Walter Citrine, I send you this line to let you know that your letter of the 31st January about bombing of towns in Spain, has been received and that I am laying it before the Prime Minister at the first opportunity. Yours sincerely, [ ] Sir Walter Citrine, K.B.E. 292/946/12a/135